Resistance Change Mechanism of Electronic Component Mounting through Contact Pressure Using Elastic Adhesive - Takashi Sato; Tomoya Koshi; Eiji Iwase (Micromachines, 2019)
For mounting electronic components through contact pressure using elastic adhesives, a high contact resistance is an inevitable issue in achieving solderless wiring in a low-temperature and low-cost process. To decrease the contact resistance, we investigated the resistance change mechanism by measuring the contact resistance with various contact pressures and copper layer thicknesses. The contact resistivity decreased to 4.2 × 10−8 Ω·m2 as the contact pressure increased to 800 kPa and the copper layer thickness decreased to 5 µm. In addition, we measured the change in the total resistance with various copper layer thicknesses, including the contact and wiring resistance, and obtained the minimum combined resistance of 123 mΩ with a copper-layer thickness of 30 µm using our mounting method. In this measurement, a low contact resistance was obtained with a 5-µm-thick copper layer and a contact pressure of 200 kPa or more; however, there is a trade-off with respect to the copper layer thickness in obtaining the minimum combined resistance because of the increasing wiring resistance. Subsequently, based on these measurements, we developed a sandwich structure to decrease the contact resistance, and a contact resistivity of 8.0 × 10−8 Ω·m2 was obtained with the proposed structure.